Optimasi Penyerapan Malachite Green Menggunakan Biosorben Kulit Matoa (Pometia pinnata) dengan Metode Batch - Dwi Hartati; Desy Kurniawati; Edi Nasra (Departemen Kimia FMIPA UNP, 2023)
This study aims to determine the optimum conditions for absorption of malachite green dye waste using matoa fruit peel biosorbent (Pometia pinnata) using a batch method with variations in particle size and contact time which will be tested with UV-Vis spectrophotometer instruments. Before being used as a biosorbent, matoa skin was activated first using 0.01 M HNO3. Activation of the biosorbent was carried out to improve the performance of the biosorbent because activation can enlarge the pores and volume of the biosorbent as well as the impurities contained in the biosorbent. The results showed that the optimum conditions for variations in particle size were 106 Âµm with an absorption capacity of 44.08 mg/g and a contact time of 90 minutes with an absorption capacity of 46.67 mg/g.